Post-Disaster Household Assessments and Eligibility Determination for Post-Disaster Social Protection Benefits - Williams, Asha (World Bank, Washington, DC, 2020)
The frequency and severity of disasters in Latin America and the Caribbean (LAC) have necessitated improving the mechanisms to identify affected individuals and households; assess post-disaster needs and conditions; and determine who will be eligible for post-disaster Social Protection (SP) support. Intended populations for different types of post disaster support vary and are often constrained by fiscal space and resource availability. Rapid increase of SP benefits to existing beneficiaries has been a common and useful SP response to support poor and vulnerable households affected by a shock. However, while LAC exhibits comparatively high coverage of SP programs among the total population and the poorest quintile when compared to other regions, there are still large coverage gaps, particularly in some countries. This further constrains rapid provision of SP benefits to non-beneficiaries or deploying emergency safety nets to affected households. Furthermore, existing SP beneficiaries are not the only persons in need of support in post-disaster contexts, as disasters often push near-poor individuals and households into poverty. This guidance note shares country experiences and provides solutions for effectively assessing post-disaster needs and conditions to inform the provision of post-disaster social protection benefits and services.